2023
DOI: 10.3390/polym15041025
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid-Coated Chitosan Nanoparticles as an Active Targeted Carrier of Alpha Mangostin for Breast Cancer Cells

Abstract: Alpha mangostin (AM) has potential anticancer properties for breast cancer. This study aims to assess the potential of chitosan nanoparticles coated with hyaluronic acid for the targeted delivery of AM (AM-CS/HA) against MCF-7 breast cancer cells. AM-CS/HA showed a spherical shape with an average diameter of 304 nm, a polydispersity index of 0.3, and a negative charge of 24.43 mV. High encapsulation efficiency (90%) and drug loading (8.5%) were achieved. AM released from AM-CS/HA at an acidic pH of 5.5 was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…The peak exhibited by hybrid PHG/HyA with a maximum at 2 θ = 16.2° was similar to those of HyA and PHG indicating the amorphous structure. 34 The partially amorphous structure of Dex was verified using XRD peaks at 2 θ around 15.2, 18.1, and 23.6°. As a result of the incorporation of Dex into the structure, the hybrid PHG/Dex gel showed peaks at 17.7° and 27.7°.…”
Section: Resultsmentioning
confidence: 99%
“…The peak exhibited by hybrid PHG/HyA with a maximum at 2 θ = 16.2° was similar to those of HyA and PHG indicating the amorphous structure. 34 The partially amorphous structure of Dex was verified using XRD peaks at 2 θ around 15.2, 18.1, and 23.6°. As a result of the incorporation of Dex into the structure, the hybrid PHG/Dex gel showed peaks at 17.7° and 27.7°.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of F-CS, two absorption bands appeared in the spectral ranges of 200-300 and 300-400 nm, which were assigned to the π-π* and n-π* transitions, respectively (Table 1) [36]. Further analysis using UV-Vis and FTIR spectroscopy confirmed the attachment of folate to CS, as indicated by the characteristic absorption bands of the amide bond in the IR spectra [23]. However, F-CS yield may be reduced due to the sequential processes required in its manufacture, such as dialysis purification.…”
Section: Characterization Of F-csmentioning
confidence: 85%
“…Nanomicelle formation and polymeric nanoparticle encapsulation have been proven to enhance the solubility of AM and facilitate its targeted delivery to specific organs [18]. Various studies, conducted both in vitro and in vivo, have demonstrated the enhanced cytotoxicity, antiproliferative activity, and induction of apoptosis when AM is delivered through these nanoparticle systems, such as transferrin-conjugated lipid-polymer hybrid NPs [19], AM-encapsulated poly(lactic-co-glycolic) acid (PLGA) NPs [20], AM-CS/sodium alginate NPs [21], AM-CS/carrageenan NPs [22] and hyaluronic acid-coated CS-NPs [23]. Additionally, NPs constructed with crosslinked CS and glyoxal have demonstrated controlled-release properties, making them a promising drug-delivery system for hydrophobic compounds such as AM [24].…”
Section: Introductionmentioning
confidence: 99%
“…8A-merge). The paramount cell internalization of HA-CMR-CS-NPs was attributed to CD44-mediated endocytosis due to interaction between HA (as a targeting ligand) and CD44 receptors overexpressed on PC-3 cells [41,42]. The presence of bright green color in the periphery of bright blue color indicates that internalized HA-CMR-CS-NPs were primarily localized in the cytoplasm around the nuclei of PC-3 cells (Fig.…”
Section: Cell Uptake E Ciencymentioning
confidence: 97%